Effect of surface textures and electrohydrodynamically atomized WS2 films on the friction and wear properties of ZrO2 coatings. Issue 1 (January 2019) - Li, Xuemu; Deng, Jianxin; Zhang, Liangliang; Liu, Yayun; Yue, Hongzhi; Duan, Ran; Ge, Dongliang
Abstract: The combination of WS2 films and surface textures were investigated for improving the friction and wear properties of sol-gel ZrO2 coatings. Grid-like grooves with different groove pitch were fabricated by laser surface texturing technology. All the textured coatings showed improved hydrophilicity (the contact angle of ZrO2 coatings decreased by 3.5–22.8% after texturing). WS2 films were deposited on the ZrO2 coatings by electrohydrodynamic atomization technology. The dry sliding friction and wear properties of samples with surface textures or/and WS2 films additive were evaluated. Both the coefficient of friction of ZrO2 coatings and steel ball wear rate were affected by laser surface texturing and WS2 films additive. The textured samples with the texture coverage of 0.679 showed the lowest friction coefficient and lowest steel ball wear rate, decreasing by 16% and 70%, respectively, when comparing with those of the untextured samples. The further improved antifriction and antiwear properties were obtained by the synergistic combination of surface textures and deposited WS2 films. Additionally, laser surface micro-texturing could contribute to prolong the WS2 films wear life and magnify its lubricating effect.